Concepts, Perception and the Dual Process Theories of Mind - Marcello Frixione; Antonio Lieto (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
In this article we argue that the problem of the relationships between concepts and perception in cognitive science is blurred by the fact that the very notion of concept is rather confused. Since it is not always clear exactly what concepts are, it is not easy to say, for example, whether and in what measure concept possession involves entertaining and manipulating perceptual representations, whether concepts are entirely different from perceptual representations, and so on. As a paradigmatic example of this state of affairs, we will start by taking into consideration the distinction between conceptual and nonconceptual content. The analysis of such a distinction will lead us to the conclusion that concept is a heterogeneous notion. Then we shall take into account the so called dual process theories of mind; this approach also points to concepts being a heterogeneous phenomenon: different aspects of conceptual competence are likely to be ascribed to different types of systems. We conclude that without a clear specification of what concepts are, the problem of the relationships between concepts and perception is somewhat ill-posed.
Keywords: concepts; perception; perceptual representation; dual process theories of mind